Development of an Integrated Students Worksheet (LKPD) for the Ternate Local Protection Project to Improve the Chemical Literacy of Senior High School Students - Liestianty, Deasy; Limatahu, Nur Asbirayani; Ibrahim, Fitriana; Nadut, Anggelinus; Limatahu, Iqbal; Roini, Chumidach; Yuliayana Napitupulu, Maria (International Journal of Integrative Sciences, 2024)
This study aims to produce integrated LKPD (student worksheets) of Ternate local potential projects to improve the chemical literacy of high school students. This study is a research and development orresearch and  development (R&D), which uses the ADDIE development model ( Analysis, Design,  Development, Implementation, and  Evaluation). The ADDIE model begins with a needs analysis conducted through a literature review and field study by means of classroom observation and questionnaire distribution. The research method used is a descriptive research method. The results of the needs analysis obtained a percentage of 100% indicating that the Ternate Local Potential Project integrated LKPD has never been used in the learning process. Furthermore, the development of the Ternate Local Potential Project integrated LKPD was designed, then tested for feasibility (validity test) by two expert teams. The validity  data obtained an average value of 3.46 with a valid category. So that the Ternate Local Potential Project integrated LKPD that was  developed has met the valid criteria and is feasible to use or can  be implemented in chemistry learning in schools so that chemical literacy can  be improved